ANALISIS INTEGRASI HARGA MINYAK KELAPA SAWIT DAN HARGA MINYAK KEDELAI DI PASAR INTERNASIONAL - Manik, Mellin; Napitupulu, Dompak; Elwamendri, Elwamendri (Universitas Jambi, 2018)
The purpose of this study was to analyze the price integration of world palm oil price and soybean oil price, and to analyze the price transmission elasticity of soybean oil price to palm oil prices. The data used in this research were secondary data in the form of time series data. This study was conducted starting 21st July 2016 until 21st August 2016. The data were analyzed by using quantitative methods. Analysis of quantitative data in this study used pre-estimation test, cointegration test, and estimation of Error Correction Model (ECM), as well as price transmission elasticity. Pre-estimation testing includes analysis of variance, correlation analysis, Granger causality test, and data stationary test. Data stationary test were using the unit root test Augmented Dickey Fuller (ADF) and Philip Perron (PP). The results of this study showed that the variable of palm oil price and soybean oil price integrated in both short and long term, it meant that changes in palm oil price was influence by changes in the price of soybean oil. A change by 1% in the price of soybean oil will affect the change in palm oil price by 0.16% in the short term and 0.53% in the long term. The price transmission elasticity of soybean oil to palm oil prices was inelastic.